Stevens Johnson Syndrome Toxic Epidermal Necrolysis Overlap Triggered by Paracetamol and Exacerbated by Cephalosporin and Fluorokuinolon: A Case Report - Retno Niken Hapsari; Marina Haroen (Jurnal Impresi Indonesia, 2025)
Stevens-Johnson Syndrome (SJS) and Toxic Epidermal Necrolysis (TEN) are rare but life-threatening type IV hypersensitivity reactions, characterized by epidermal necrolysis, bules, skin desquamation, and mucosal involvement. Most cases are triggered by medications, with a fairly high mortality rate, especially in TEN. Management requires discontinuation of trigger medications as early as possible, a multidisciplinary approach, and intensive supportive therapy. It was reported that a 40-year-old Russian man with complaints of peeling skin almost all over the body, pain, burning sensation, accompanied by eye and lip disorders. Complaints arise after the consumption of paracetamol and worsen after the administration of ceftriaxone and levofloxacin. Physical examination showed extensive skin and mucosal involvement with a positive Nikolsky mark, BSA 32%. Laboratory tests showed leukocytosis and increased CRP. The diagnosis of SJS is established with the suspected cause of these drugs. Patients receive supportive therapy including antibiotic discontinuation, rehydration, corticosteroids, antihistamines, mucosal protection, wound care, as well as consultations with ophthalmologists and ENTs. The management of SJS requires discontinuation of trigger drugs as early as possible, intensive supportive therapy, and multidisciplinary coordination to reduce complications and mortality.